تكلفة التمويل وأثرها في قيمة المؤسسة مع فرص نمو مختلفة - دراسة قياسية للمؤسسات المسعرة في بورصة عمان للأوراق المالية- - قريني, وردة; بورديمة, سعيدة (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى معرفة أثر تكلفة التمويل في قيمة المؤسسة، وذلك مع فرص النمو المختلفة، حيث تم إجراؤها على عينتين من المؤسسات المسعرة في بورصة عمان للأوراق المالية سنة 2019، عينة لديها فرص نمو مرتفعة، والأخرى لديها فرص نمو منخفضة. وتوصلت إلى مجموعة من النتائج أهمها أن أثر تكلفة التمويل في قيمة المؤسسة كان سلبيا بغض النظر عن اختلاف فرص النمو، وأن تكلفة التمويل كانت مرتفعة في المؤسسات التي لديها انخفاضا في فرص النمو، ومنخفضة في المؤسسات التي لديها ارتفاعا في فرص النمو، ما انعكس على قيمة المؤسسة حيث كانت منخفضة في المؤسسات ذات فرص النمو المنخفضة، ومرتفعة في المؤسسات ذات فرص النمو المرتفعة. This study aims to know the impact of the cost of funding on the value of the firm, with different growth opportunities, as it was conducted on two samples of companies quoted on the Amman Stock Exchange in 2019, one sample with high growth opportunities, and the other with low growth opportunities. The study reached a set of results, the most important of which is that the impact of the cost of funding on the value of the firm was negative regardless of the different opportunities for growth, and that the cost of funding was high in firms that have low growth opportunities, and low in firms that have a rise in growth opportunities, which was reflected on firm value, it was low in companies with low growth opportunities, and high in companies with high growth opportunities.
The cost of funding and its impact on the value of the firm with different growth opportunities - A standard study for the companies quoted on the Amman Stock Exchange
مقال
Keywords: تكلفة التمويل ; قيمة المؤسسة ; فرص النمو ; حقوق الملكية ; الهيكل المالي